MicroRNAs as regulators of cardiac dysfunction in sepsis: pathogenesis and diagnostic potential - Liu, Zhen; Li, Feiyang; Li, Ningcen; Chen, Yong; Chen, Zelin (Frontiers in Cardiovascular Medicine, 2025)
IntroductionSepsis, a life-threatening condition arising from an uncontrolled immune response to infection, can lead to organ dysfunction, with severe inflammation potentially causing multiple organ failures. Sepsis-induced cardiac dysfunction (SIMD) is a common and severe complication of sepsis, significantly increasing patient mortality. Understanding the pathogenesis of SIMD is crucial for improving treatment, and microRNAs (miRNAs) have emerged as important regulators in this process.MethodsA comprehensive literature search was conducted in PubMed, Science Direct, and Embase databases up to September 2024. The search terms included [“miRNA” or “microRNA”] and [“Cardiac” or “Heart”] and [“Sepsis” or “Septic”], with the language limited to English. After initial filtering by the database search engine, Excel software was used to further screen references. Duplicate articles, those without abstracts or full texts, and review/meta-analyses or non-English articles were excluded. Finally, 106 relevant research articles were included for data extraction and analysis.ResultsThe pathogenesis of SIMD is complex and involves mitochondrial dysfunction, oxidative stress, cardiomyocyte apoptosis and pyroptosis, dysregulation of myocardial calcium homeostasis, myocardial inhibitory factors, autonomic nervous regulation disorders, hemodynamic changes, and myocardial structural alterations. miRNAs play diverse roles in SIMD. They are involved in regulating the above-mentioned pathological processes.DiscussionAlthough significant progress has been made in understanding the role of miRNAs in SIMD, there are still challenges. Some studies on the pathogenesis of SIMD have limitations such as small sample sizes and failure to account for confounding factors. Research on miRNAs also faces issues like inconsistent measurement techniques and unclear miRNA-target gene relationships. Moreover, the translation of miRNA-based research into clinical applications is hindered by problems related to miRNA stability, delivery mechanisms, off-target effects, and long-term safety. In conclusion, miRNAs play a significant role in the pathogenesis of SIMD and have potential as diagnostic biomarkers. Further research is needed to overcome existing challenges and fully exploit the potential of miRNAs in the diagnosis and treatment of SIMD.